Domain pattern formation and kinetics on ferroelectric surfaces under thermal cycling using scanning force microscopy - V. Likodimos; Labardi, M.; Allegrini, M. (Physical Review B - Condensed Matter and Materials Physics, 2002)
Scanning force microscopy in the dynamic contact mode with resonance enhanced domain contrast is applied to study in situ pattern formation and relaxation kinetics of ferroelectric domains on the cleavage surface of triglycine sulfate subjected to successive annealing-cooling cycles. Substantial differences in the domain morphology and kinetics are disclosed upon cooling at temperatures close to Tc. Convolution of stripe domains with residual domain nuclei and random pinning forces due to intrinsic defects are suggested to account for variations in the domain structure and slowing down of domain kinetics.